Pengaruh Kepemimpinan Partisipatif dan Komitmen Kerja terhadap Kinerja Guru SMK Negeri di Kota Prabumulih - Yusrianto Yusrianto; Alhadi Alhadi; Andi Rahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the influence of participative leadership and work commitment on the performance of State Vocational School teachers in Prabumulih City. From the results of researchers' observations and interviews with several fellow teachers and principals at State Vocational Schools in Prabumulih City, some still have a low work commitment, and teachers are committed to exemplary work. Apart from that, several research results show the leadership role of the head schools in improving teacher performance, especially after the COVID-19 pandemic. This quantitative research will analyze the influence of participative leadership and work commitment on the performance of State Vocational School teachers throughout Prabumulih City. A questionnaire instrument with a Likert scale was used. A sample of 153 people was taken using the Slovin method from a population of 248 teachers at State Vocational Schools in Prabumulih City. The descriptive statistical analysis results show that each variable's norm range values are relatively good. Inferential inferential statistics tests hypotheses using simple linear regression and multiple linear regression. The conclusion is that participative leadership and work commitment positively influence teacher performance in State Vocational Schools throughout Prabumulih City. Keywords: Leadership, Work Commitment, Performance